Influence of Mn and Co doping on optical and magnetic properties in 3C–SiC. (June 2021) - Lin, Long; Yao, Linwei; Li, Shaofei; Shi, Zhengguang; Xie, Kun; Huang, Jingtao; Tao, Hualong; Zhang, Zhi
Abstract: Diluted magnetic semiconductors with magneto-optical properties have very attractive properties in many applications (optical magnetic modulation). However, the major challenge limiting its further development is the ability to have excellent optical properties at room temperature. Through the first principle calculation of GGA + U method based on DFT calculation, we systematically calculated the electronic structure, magnetic properties and optical properties of Mn, Co and (Mn, Co) doped 3C–SiC. By (Mn, Co) co-doped 3C–SiC, we found that the system not only can obtain high total magnetic moment, but also has ferromagnetism, and the maximum Curie temperature reaches 886 K. The reason of ferromagnetism is because these ferromagnetic states are caused by p - d hybridization between adjacent C atoms and Mn and Co atoms. In addition, we found that the vacancy defect has an effect on the ferromagnetism, which is larger when the vacancy distance dopant is 4.007 Å. At its theoretical temperature we found that the three doping systems showed a significant red shift relative to the intrinsic system. The Si31 MnC32 system has the strongest absorption capacity for infrared light and ultraviolet light, while the Si30 MoCoC32 system has the strongest absorption capacity for visible light. The results provide a good candidate for magnetic origin and optics. Highlights: (Mn, Co) co-doped 3C-SiC system has higher total magnetic moment and better room temperature ferromagnetism. The magnetic coupling induced by Mn and CO doping is due to the interaction of p-d hybridization. The doping system has a significant red shift compared with the intrinsic system, and the Si30 MnCoC32 system has the strongest absorption capacity for visible light.